Combination of noninvasive imaging techniques to characterize pigments in Buddhist thangka paintings. (14th September 2020) - Brocchieri, Jessica; de Viguerie, Laurence; Sabbarese, Carlo; Boyer, Marion
Abstract : Scanning macro‐XRF, XRF point measurements and hyperspectral reflectance imaging in the visible and near‐infrared range were combined to characterize the pigments of a Tibetan painting. The complementary use of the different investigation techniques allowed us to (a) clearly identify the pigments used by the artist, (b) strengthen the few data present in historical and contemporary sources and (c) provide data necessary for any accurate conservation treatment of the painting. The proposed methodology allows an in‐depth characterization of the materials used in thangkas, with the identification of all the pigments used by Tibetan artists, as shown by the analyses of reference samples. In the present study traditional pigments, commonly cited in historical sources, were identified such as vermilion, minium, orpiment and azurite, but also more unusual compounds such as brochantite and antlerite (in blue/green areas). Elemental distribution images confirmed that some parts of the thangka were restored, without taking into account the original pigments or the original design. Underlying annotations and a carbon black under‐drawing were highlighted by the application of near‐infrared hyperspectral imaging technique, which proved to be particularly useful for the study of such paintings.